Justice for Palestine: A Call to Action from Indigenous & Women of Color Feminists - The People's Forum NYC (2021)
We come together on the 10th anniversary of our last day in Palestine, hundreds of presentations, articles, panels, and interventions later, to offer our Report Card reaffirming the relevance and urgency of re-telling stories of apartheid, ethnic cleansing, and settler colonialism and of Palestinian steadfastness, resistance and resilience. SPEAKERS: Dr. Angela Davis Dr. Anna Guevarra Dr. Barbara Ransby Dr. Beverly Guy-Sheftall Dr. Chandra Talpade Mohanty Dr. Gina Dent Dr. G. Melissa Garcia Dr. Rabab Abdulhadi Dr. Waziyatawin Co-sponsored by Arab and Muslim Ethnicities and Diaspora Studies
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; afro-féminisme; approches et analyses; asie; cours; discipline; féminisme autochtone; féminisme décolonial; féminisme islamique; féminismes noirs; génocide; histoire et politique; militance; palestine; pol4212; premier cycle; périodes historiques; régions géographiques; science politique; science politique et droit; système colonial; systèmes d'oppressions; thématiques; études arabes; études décoloniales

Queer of Color Critique - Lakhani, Shreeta (lambda nordica, 2020)
Keywords: 2000 à aujourd'hui; 2010-2019; 2020-2029; LGBTQIA2+; afro-féminisme; approches et analyses; cours; discipline; féminismes noirs; histoire et politique; homonationalisme; intersectionnalité; pol4212; premier cycle; périodes historiques; queer; queer of color; science politique; science politique et droit; thématiques; études de genres

Gender Equality in the New Millennium: Goal or Gimmick? - ANTROBUS, PEGGY (Caribbean Quarterly, 2006)
At the Millennium Summit in September 2000 the largest gathering of world leaders adopted the UN Millennium Declaration, committing their nations to a new global partnership to reduce extreme poverty and setting out a series of time-bound targets, all with a deadline of 2015, that have become known as the Millennium Development Goals (MDGs). The Millenium Development Goals are now part of an international development framework which many countries in the Caribbean have signed on to. This paper addresses the question of how the Millenium Development Goals can be made to work to promote gender equality and empowerment in the Caribbean Community (CARICOM) region. The analysis here will not be limited to "gender equality and women's empowerment (MDG Goal 3). It will also highlight the gender dimensions of some of the other MDGs that closely related to women's equality and empowerment - as a means and as an outcome. Finally, the analysis and suggestions in relation to strategies "to ensure that gender inequalities are identified and addressed in the MDG monitoring process and in national policy responses from governments" will focus on Caribbean realities. Suggestions are made by drawing on the findings and insights on the linkages between global trends, development strategies (including the macroeconomic policy framework of structural adjustment) and their impact on poor women, and the ways in which we might now approach activist interventions toward the goal of gender equality and women's empowerment.
Keywords: 2000 à aujourd'hui; 2000-2009; afro-féminisme; amériques; approches et analyses; caraïbes; cours; discipline; féminisme des caraïbes; féminismes noirs; histoire et politique; pol4022; premier cycle; pédagogie; périodes historiques; ressource en ligne; régions géographiques; science politique; science politique et droit; sciences de l'éducation; thématiques